The Power of the Written Voice - Beck, Terry (Analytic Teaching, 2014)
Introduction:  I sit in a straight-backed wooden chair, an open book lying flat on the desk in front of me, a pen in my hand and a transparent 6" ruler nearby for sharp underlines.  Early morning sunlight streams in the window at my shoulder.  A voice speaks from the page: